Are industrial policy instruments effective? A review of the evidence in OECD countries - Criscuolo, Chiara (OECD Publishing, 2022)
While the case for industrial policy is gaining traction across OECD countries, little consensus exists on the effectiveness of such interventions. Building on a new analytical framework for industrial policy developed in a companion paper, this paper reviews the empirical literature on the effectiveness of industrial policy instruments, laying out the knowns and unknowns. Overall, it strongly supports the premise that well-designed economic incentives for firms and good framework conditions shaping the business environment are effective. At the same time, it emphasises the limited and inconclusive nature of the evidence regarding the increasingly frequent targeted and demand-side instruments. Finally, it underlines the complementarities between economic incentives and other interventions such as skill policies or framework conditions, notably competition and trade policies. Framework conditions are indeed key in enabling the most productive firms to grow and an important channel for structural change
Keywords: Science and Technology